A conversation between Pablo Arrocha Olabuenaga and Naz Khatoon Modirzadeh on the origins, objectives, and context of the 24 February 2021 'Arria-formula' meeting convened by Mexico. (3rd July 2021) - Modirzadeh, Naz K.; Olabuenaga, Pablo Arrocha
ABSTRACT: A conversation between Pablo Arrocha Olabuenaga and Naz Khatoon Modirzadeh on the origins, objectives, and context of the 24 February 2021 'Arria-formula' meeting convened by Mexico.